MEASURING THE AVAILABILITY AND VALIDATION OF ISLAMIC MARKETING: A THEORETICAL AND EMPIRICAL STUDY - Yusrizal Yusrizal; Mira Chairani; Nurma Sari (Pena Cendekia Insani, 2026)
This research aims to analyze the availability and validation of the Islamic marketing model thru theoretical and empirical approaches based on the principles of maqasid al-shariah. In the last two decades, Islamic economic growth has shown a significant trend across various sectors, but the practice and research of Islamic marketing still face constraints in the validity and availability of valid measurement instruments. This study uses a systematic literature review method on Scopus and DOAJ indexed articles from 2014–2025, focusing on Islamic marketing indicators and compliance. The study results indicate that Islamic marketing does not yet have a comprehensive conceptual framework capable of fully integrating functional and spiritual dimensions. The application of maqasid al-shariah is an important foundation that emphasizes that marketing activities must be directed toward the common good, justice, and sustainability. By integrating Sharia principles into the nine elements of the product marketing mix (9Ps) – product, price, place, promotion, people, process, physical evidence, promise, and patience – a conceptual model was obtained that places ethics, spirituality, and Sharia compliance at the core of the marketing strategy. This research is expected to serve as a theoretical foundation for the development of empirical validation instruments and practical guidelines for companies to implement authentic and welfare-oriented Islamic marketing.